2018
DOI: 10.1016/j.camwa.2018.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic models for the electric potential across a highly conductive casing

Abstract: We analyze a configuration that involves a steel-cased borehole, where the casing that covers the borehole is considered as a highly conductive thin layer. We develop an asymptotic method for deriving reduced problems capable of efficiently dealing with the numerical difficulties caused by the casing when applying traditional numerical methods. We derive several reduced models by employing two different approaches, each of them leading to different classes of models. We prove stability and convergence results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Fourth-order Gap-ITCs model. In [5] it is observed that the choice of Impedance Transmission Conditions (ITCs) can lead to different asymptotics models. One of the proposed methods consists of computing the solution in the reduced domain Ω ε := R 3 \ Ω ε lay , thus the name Gap-ITCs.…”
Section: 31mentioning
confidence: 99%
See 4 more Smart Citations
“…Fourth-order Gap-ITCs model. In [5] it is observed that the choice of Impedance Transmission Conditions (ITCs) can lead to different asymptotics models. One of the proposed methods consists of computing the solution in the reduced domain Ω ε := R 3 \ Ω ε lay , thus the name Gap-ITCs.…”
Section: 31mentioning
confidence: 99%
“…In that case, the high conductivity of the casing, along with its thinness, greatly complicates numerical simulations. A natural way to circumvent this drawback is to consider asymptotic models avoiding the problems created by the casing [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations